Accounting for non-accounting students - Dyson, J. R. [ (John R.)] (Financial Times Prentice Hall, 2007)
This book is traditional in approach and covers both financial & management accounting. This edition has been streamlined: long & difficult chapters have been simplified, case studies have been added & further subdivisions make the book more flexible